EKSPLORASI LINTASAN BELAJAR MATERI POLA BILANGAN DENGAN KONTEKS Q.S. AL-ANFAL AYAT 66 - Nurhasanah Nurhasanah; Sugiatno Sugiatno; Asep Nursangaji; Zubaidah R; Rustam Rustam (UNIVERSITAS TANJUNGPURA, 2023)
The study's objective was to describe the learning trajectory of number pattern material in the context of Q.S Al-Anfal verse 66. At MTS Basiuni Imran Sambas, 26 eighth grade students participated in this study. This study uses design research as its method. Design research consists of three stages: preparing for the experiment, experiment design, and retrospective analysis. Written tests and interviews were used to collect data, which were then analyzed and revised to obtain the actual learning trajectory. This research produced a learning trajectory that included several activities, namely (1) reading the translation of Q.S Al Anfal verse 66; (2) fill in the table; (3) observing the column for the number of patient people and the column for the number of enemies to see the relationship between the two; (4) calculate the number of enemies that can be defeated if you know the number of patient people or vice versa; (5) looking for an unknown value to find the general formula for an even number pattern.